Future time perspective: Dimensions of opportunities, life, and time are differentially associated with physical health, cognitive functioning, and well-being in old age. (1st September 2020) - Kozik, Pavel; Drewelies, Johanna; Düzel, Sandra; Demuth, Ilja; Steinhagen-Thiessen, Elisabeth; Gerstorf, Denis; Hoppmann, Christiane A.
Abstract: Objective : The present study investigated the multidimensional nature of the future time perspective scale and dimension-specific associations with measures of physical health, cognitive functioning, and well-being. Method : Using data from the Berlin Aging Study II ( N  = 1, 038, M age = 71 years, range = 61–88 years, 52% women), different models of future time perspective were compared using confirmatory factor analyses, and the best-fitting model was then used to explore dimension-specific associations with physical health, cognitive functioning, and well-being measures. Results : A model of future time perspective composed of a focus on opportunities, a focus on life, and a focus on time was found to have the best fit. An extended focus on opportunities was associated with stronger grip strength, more accurate memory, as well as higher life satisfaction and positive affect. An extended focus on time was associated with less accurate memory, lower negative affect, and greater life satisfaction. A focus on life was unrelated to study measures. Discussion : Findings suggest that future time perspective is multidimensional and that these dimensions are differentially associated with physical health, cognitive functioning, and well-being in old age.